2008
DOI: 10.1136/emj.2007.050914
|View full text |Cite
|
Sign up to set email alerts
|

Morphine analgesia in patients with acute appendicitis: a randomised double-blind clinical trial

Abstract: NCT00477061.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 22 publications
(26 reference statements)
1
17
0
Order By: Relevance
“…38 Still, we believe that 14% remains unacceptably high; ample evidence currently supports the pre-diagnostic administration of analgesia. 13,14,[39][40][41][42][43][44][45][46] Furthermore, although the proportion of respondents withholding analgesia due to the belief it may mask a surgical diagnosis is significantly lower than reported in other studies, it still portends a delayed approach to providing analgesia in children with abdominal pain and emphasizes the need for wider knowledge translation. Although the majority of respondents indicated they would provide analgesia in an appendicitis scenario (and AAP recommends to provide systemic opioids for severe pain 40 ), less than two-thirds of survey respondents reported a willingness to provide intravenous opioids, despite a pain score of 8 out of 10.…”
Section: Discussionmentioning
confidence: 99%
“…38 Still, we believe that 14% remains unacceptably high; ample evidence currently supports the pre-diagnostic administration of analgesia. 13,14,[39][40][41][42][43][44][45][46] Furthermore, although the proportion of respondents withholding analgesia due to the belief it may mask a surgical diagnosis is significantly lower than reported in other studies, it still portends a delayed approach to providing analgesia in children with abdominal pain and emphasizes the need for wider knowledge translation. Although the majority of respondents indicated they would provide analgesia in an appendicitis scenario (and AAP recommends to provide systemic opioids for severe pain 40 ), less than two-thirds of survey respondents reported a willingness to provide intravenous opioids, despite a pain score of 8 out of 10.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (Attard et al, 1992;Pace and Burke, 1996;LoVecchio et al, 1997;Vermeulen et al, 1999;Mahadevan and Graff, 2000;Thomas et al, 2003;Gallagher et al, 2006;Amoli et al, 2008) and one Cochrane review published in 2007 (Manterola et al, 2007), which was updated in 2011 (Manterola et al, 2011), have demonstrated that administering analgesia for acute abdominal pain is appropriate prior to the diagnosis regardless of the aetiology of the abdominal pain. The authors of the Cochrane review concluded that the use of opioid analgesics neither increased the risk of misdiagnosis nor increased the risk of incorrect treatment decisions being made; the Cochrane reviewers furthermore stated that pain therapy may, in fact, make the clinical examination easier in patients with an acute abdomen.…”
Section: Pre-diagnostic Analgesiamentioning
confidence: 99%
“…One-dimensional scales such as the visual analogue scale (VAS), verbal rating scale (VRS) and numerical rating scale (NRS), as well as the 'Smiley analogue scale' (SAS) are used in the acute setting ( Fig. 1) (Todd et al, 1996;Kelly, 1998;Gallagher et al, 2001;Marinsek et al, 2007;Amoli et al, 2008;Daoust et al, 2008;Jawaid et al, 2009;Sharwood and Babl, 2009). Limitations for pain measurement include disturbances of consciousness, impaired vision and language barriers (Gallagher et al, 2001).…”
Section: Pain Intensity Assessmentmentioning
confidence: 99%
See 2 more Smart Citations